2019
DOI: 10.4103/ijo.ijo_300_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flanged intrascleral intraocular lens fixation versus iris claw intraocular lens fixation: A retrospective study

Abstract: Purpose:To compare the visual outcome and complications of retropupillary fixated iris claw intraocular lens (IOL) and sutureless intrascleral IOL fixation using the flanged fixation technique at 1 year.Methods:In this retrospective study, eyes that underwent either iris claw or flanged SFIOL from January 2016 to July 2017 with a minimum of 1-year follow-up were enrolled. Improvement in visual acuity, intraocular pressure measurements, endothelial cell count, central macular thickness, and complications were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 17 publications
1
63
0
2
Order By: Relevance
“…ECC loss after surgery can be caused by contact with surgical instruments and IOL during surgery and by the toxic effects of inflammatory mediators [ 22 ]. In previous studies, there was no significant difference in postoperative ECC between scleral fixation and RP-IOL implantation and between RP-IOL implantation and ISF; a decrease in postoperative ECC was observed in all three groups [ 23 , 24 ]. The results of this study were consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…ECC loss after surgery can be caused by contact with surgical instruments and IOL during surgery and by the toxic effects of inflammatory mediators [ 22 ]. In previous studies, there was no significant difference in postoperative ECC between scleral fixation and RP-IOL implantation and between RP-IOL implantation and ISF; a decrease in postoperative ECC was observed in all three groups [ 23 , 24 ]. The results of this study were consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…Advancements of sutureless SF IOLs include the recently introduced and widely adopted sutureless SF IOL technique with a flange, which has provided excellent outcomes. 6,25 A recent American Academy of Ophthalmology's Ophthalmic Technology Assessment by Shen et al compared the visual acuity and safety profile of different IOL techniques. The study did not find a significant difference in visual acuity outcomes when evaluating scleral fixation and iris fixation techniques.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Kelkar et al, in their retrospective comparative study, experienced a transient rise of IOP more in eyes with scleral-fixated IOL (17%) than ICIOL (8%), which was managed with topical therapy. 49 Nevertheless, Madhivanan et al found that eyes with ICIOL (10%) experienced greater transient IOP spikes due to iritis than eyes with scleral-fixated IOL (0%). 55 …”
Section: Postoperative Outcomesmentioning
confidence: 97%
“… 68 Studies on retropupillary ICIOL have shown a considerable variation in ECL ranging from 3%-43%. 14–16 , 23 , 25 , 27 , 28 , 30–33 , 36 , 42–44 , 46 , 47 , 49–51 , 56 Dalby et al, in a prospective comparative clinical trial, observed no significant difference in ECL following ICIOL implantation (15%) and IOL repositioning (18%) for late in-the-bag IOL dislocation at the end of 2 years. 64 In contrast, Kristianslund et al reported a significant postoperative ECL of 10% in the ICIOL group and a non-significant postoperative ECL of 3% in the repositioning group.…”
Section: Postoperative Outcomesmentioning
confidence: 98%